Influence of heat treatment on the tensile properties and fatigue properties of Mg-8.8Gd-3.5Y-1.5Zn-0.5Zr alloy. (21st May 2021) - Cui, Ya; Shi, Yusha; Zheng, Jie; Yan, Zhaoming; Zhang, Jishi; Zhang, Zhimin; Wang, Qiang; Xue, Yong
Abstract: The microstructure, tensile properties and fatigue properties of Mg- 8.8Gd- 3.5Y- 1.5Zn- 0.5Zr alloy under T4 and T6 heat treatment have been studied. The as-cast alloy was homogenized to eliminate the inhomogeneous structure and the strength of the alloy was increased by aging treatment. The microstructure evolution and mechanical properties of the alloy were investigated by optical microscope, scanning electron microscope, energy dispersive spectrometer and universal mechanical testing machine. The as-cast alloy is composed of dendritic α -Mg matrix, metastable lamellar stacking fault, eutectic Mg24 (Gd, Y, Zn)5, massive long-period stacking ordered (LPSO) phase Mg12 (Gd, Y)Zn and a few rare earth rich phases. In the process of homogenization, the lamellar phase and Mg24 (Gd, Y, Zn)5 eutectic phase dissolved in the α -Mg matrix gradually, and the massive LPSO phase disappeared gradually, while the lamellar LPSO phase steadily grew into grains and formed some precipitate particles near the grain boundary. As the tensile temperature increases, the ductility of solid solution alloy increases, but decreases at 250 °C, which is related to the melting reaction of γ phase at high temperature and the cracking caused by grain boundary sliding. Intergranular fracture occurs at 250 °C. When the tensile temperature rises to 150 °C, the ultimate tensile strength of the alloy increases first before 150 °C and decreases after 150 °C, which is related to two strengthening mechanisms, namely, dissolution of Gd and Y elements into α -Mg matrix results in solid solution strengthening and the co-lattice strengthening between petal β ′ and α -Mg matrix. Compared with the fatigue properties of the alloy after solution treatment and aging treatment, the fatigue life of the alloy after aging treatment is longer.